Organ Trafficking and Transplant Tourism: The Role of Global Professional Ethical Standards-The 2008 Declaration of Istanbul - Danovitch, Gabriel M (LIPPINCOTT WILLIAMS & WILKINS, 2022)
10.1097/TP.0b013e318295ee7d